THE APPLICATION OF SAPTA PESONA IN THE SAKAI TRIBE TRADITIONAL HOUSE TOURISM OBJECT, KESUMBO AMPAI VILLAGE, BATHIN SOLAPAN DISTRICT, BENGKALIS REGENCY - Farhoney, Talitha; ", Musadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Sapta Pesona is a condition that must be realized in every tourism product so that it can attract tourists to visit an area. One of the attractions that tourists visit is low so that it requires the application of Sapta Pesona in the Sakai tribe traditional house, Kesumbo Ampai Village, Bathin Solapan District, Bengkalis Regency. Therefore this study aims to determine the application of Sapta Pesona in the Sakai Traditional House Tourism Object of Kesumbo Ampai Village, Bathin Solapan District, Bengkalis Regency and the Public Attitude Toward the Existence of Sakai Traditional House Tourism Object. The research will be known and measured by quantitative descriptive methods. This study took samples of 80 respondents taken using the theory of Singarimbun. Data collection techniques in this study used observation, questionnaires, documentation, interviews. To measure the data interval in this study using a Likert scale. Based on the results of the study showed that the application of Sapta Pesona in the Object of the Sakai Tribal Traditional House Kesumbo Ampai Village Bathin Solapan District Bengkalis. Regency included in the good category and the Public Attitude Towards the Existence of the Object of the Sakai Tribal Traditional House supports the Object of the Sakai Tribal Traditional House.  Keywords : Sapta Pesona, Traditional House of the Sakai Tribe, Attraction